Neuplatonisches Gedankengut in den "Homilien über die Seligpreisungen" Gregors von Nyssa - Lilla, Salvatore Romano Clemente. (Vigiliae Christianae, Supplements, 2004)
This volume thoroughly analyses the Neoplatonic sources and background of Gregory of Nyssa's eight Homilies on the Beatitudes according to the most preeminent themes: human virtue, knowledge of God and Self, negative theology, God's sublimity, ἀπάθεια and ὁμοιώσις, the mutual relationship of the virtues, the Logos as physician, the essence of beauty, the contemplation of the universe, unification. The study complements the first commentary of the homilies published in Supplements to Vigiliae Christianae volume 52 and provides a deep and rich mine of specialised knowledge in a field that is particularly important for the understanding of Gregory's thought.